A pastoral investigation of the phrase ‘go tloša Setšhila’ [traditional purification] as the last phase in the process of bereavement mourning amongst the Basotho - Letšosa, Rantoa Simon (Verbum et ecclesia, 2011)
This article investigates and attempts to provide answers from pastoral perspectives regarding the perception the Basotho have on the issue of traditional purification. The aim of this article is to find out why the bereaved, that have not yet been purified traditionally, are not allowed to be part of certain activities, like going to the church and also performing certain community activities.The investigation was conducted by way of qualitative research. Three different Sotho Reformed congregations were selected, namely one from the Northern-Sotho speaking congregations, one from the Setswana speaking congregations and one from the Southern-Sesotho speaking congregations. Respondents included one minister, one older man, one older woman, and two young members including a man and a woman from each congregation in order to get a broader perspective. For the sake of confidentiality the names of the congregations and participants remained anonymous.The results of the article indicate that the rights of the bereaved to perform certain duties in the community are reduced till such time that they are purified traditionally.